Circ-UQCRC2 aggravates lipopolysaccharide-induced injury in human bronchial epithelioid cells via targeting miR-495-3p/MYD88-mediated inflammatory response and oxidative stress - Xuan Zhang; Chunbao Chen; Bei Li; Wei Lu (Taylor & Francis Group, 2021)
Infantile pneumonia is a common inflammatory disease with the infections of various pathogens in lower respiratory tracts. Here, the role and working mechanism of circular RNA (circRNA) ubiquinol-cytochrome c reductase core protein 2 (circ-UQCRC2; hsa_circ_0038467) in infantile pneumonia were investigated. Cell viability, apoptosis, and inflammatory response were assessed by 3-(4,5-dimethyl-thiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, flow cytometry, and enzyme-linked immunosorbent assay (ELISA). Cell oxidative stress was analyzed by measuring the production of malondialdehyde (MDA) and superoxide dismutase (SOD). Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and Western blot assay were performed to determine the expression of RNAs and proteins. Dual-luciferase reporter assay and RNA immunoprecipitation (RIP) assay were performed to confirm the interaction between microRNA-495-3p (miR-495-3p) and circ-UQCRC2 or myeloid differentiation primary response protein 88 (MYD88). Lipopolysaccharide (LPS) treatment suppressed the viability while induced the apoptosis, inflammation, and oxidative stress of 16HBE cells in a dose-dependent manner. LPS exposure dose-dependently up-regulated the expression of circ-UQCRC2 in 16HBE cells. Circ-UQCRC2 absence attenuated LPS-induced injury in 16HBE cells. miR-495-3p was a target of circ-UQCRC2, and circ-UQCRC2 silencing-mediated protective effects in LPS-induced 16HBE cells were partly reversed by anti-miR-495-3p. MYD88 was a target of miR-495-3p, and MYD88 overexpression partly counteracted miR-495-3p accumulation-mediated influences in 16HBE cells upon LPS exposure. Circ-UQCRC2 interference decreased the protein expression of MYD88 partly by up-regulating miR-495-3p in LPS-induced 16HBE cells. In conclusion, circ-UQCRC2 contributed to LPS-induced injury of 16HBE cells by targeting miR-495-3p/MYD88 signalling-mediated inflammatory response and oxidative stress.